PAGES OF HISTORY OF THE CHAIR OF ANALYTICAL, PHYSICAL AND COLLOIDAL CHEMISTRY OF PHARMACEUTICAL FACULTY OF THE I.M. SECHENOV FIRST MSMU - Yu. Ya. Kharitonov; M. S. Sergeeva (Сеченовский вестник, 2022)
This article deals with the history of creation of the chair of analytical, physical and colloidal chemistry of pharmaceutical faculty. The main historical stages which are connected with association of chairs of the general and inorganic chemistry, physical and colloidal chemistry, analytical chemistry are considered. The main directions of research work of chairs are analyzed and also activity of scientific schools is studied.